Making Mala: Malaita in Solomon Islands, 1870s – 1930s. (25th March 2018) - Frazer, Ian
Abstract : Making Mala: Malaita in Solomon Islands, 1870s – 1930s . By Clive Moore (Canberra: ANU Press (Pacific Series), 2017), pp. xxvii + 550. Seventeen Maps. AU$68.00 (pb).